Approximations of classes $B^{Ω}_{p,θ}$ of functions of many variables by entire functions in the space $L_q (R^d)$ - Yanchenko, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
Exact-order estimates are obtained for the best approximations of the classes $B^{Ω}_{p,θ}$ of functions of many variables by entire functions of the exponential type in the space $L_q (R^d)$.